Reinforcing Deterrence on NATO's Eastern Flank Wargaming the Defense of the Baltics - Shlapak, David A. (RAND Corporation, 2016)
Russia's recent aggression against Ukraine has disrupted nearly a generation of relative peace and stability between Moscow and its Western neighbors and raised concerns about its larger intentions. This report describes the implications of a series of war games that examined the threat Russia may present to the three Baltic republics-Estonia, Latvia, and Lithuania-former Soviet republics, now NATO member states that border Russian territory.